Electrochemical Studies of LbL Films With Dawson Type Heteropolyanion Glassy Carbon Electrode Sensor Modified for Methyl Parathion Detection - Ditta, Nafeesa Allah; Yaqub, Mustansara; Nadeem, Sohail; Jamil, Sundas; Hassan, Sadaf Ul; Iqbal, Shahid; Javed, Mohsin; Elkaeed, Eslam B.; Alshammari, Fwzah H.; Alwadai, Norah; Alzhrani, Rami M.; Awwad, Nasser S.; et al. (Frontiers in Materials, 2022)
Rapid detection of methyl parathion was measured by using a fabricated glassy carbon electrode (GCE) sensor which was designed by the layer by layer (LBL) method. Multilayers assemblies were developed on the glassy carbon electrode by alternating depositions of anions and cations in which a Dawson Type Polyoxometalate β-K6[(P2W18O62·H2O)]·14H2O ( P2W18 POM)